2014
DOI: 10.5935/1518-0557.20140005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and anatomy of cardiac malformations in children conceived by assisted reproduction techniques - A review

Abstract: The aim of this study is to identify the occurrence of cardiac malformations occurred in children conceived by assisted reproduction techniques (ART) in the international literature in Medline database from 1999 to 2012. The search returned data on 32,000 births, whose 21,000 were conceived naturally and 11,000 were conceived by ICSI and/or IVF. The incidence of cardiac malformations in general population situations was 0.4%. The incidence of cardiac malformations by ART was 1.8% from ICSI and IVF. Among the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A recent study reported the incidence of cardiac malformations using different search terms related to cardiac malformations and/or ARTs in the Medline database for the years 1999 to 2012. The search returned data on 32,000 births (21,000 naturally conceived; 11,000 conceived through ART) [ 216 ]. Cardiac malformations occurred in 1.8% (198 cases) of births conceived through ART compared to 0.4% (88 cases) of births in the general population [ 216 ].…”
Section: What Is the Evidence That Arts Influence Cardiovascular Hmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported the incidence of cardiac malformations using different search terms related to cardiac malformations and/or ARTs in the Medline database for the years 1999 to 2012. The search returned data on 32,000 births (21,000 naturally conceived; 11,000 conceived through ART) [ 216 ]. Cardiac malformations occurred in 1.8% (198 cases) of births conceived through ART compared to 0.4% (88 cases) of births in the general population [ 216 ].…”
Section: What Is the Evidence That Arts Influence Cardiovascular Hmentioning
confidence: 99%
“…The search returned data on 32,000 births (21,000 naturally conceived; 11,000 conceived through ART) [ 216 ]. Cardiac malformations occurred in 1.8% (198 cases) of births conceived through ART compared to 0.4% (88 cases) of births in the general population [ 216 ]. Comparing the incidence of specific forms of cardiovascular disorders from a total of 11,000 pregnancies in ART children and 21,000 pregnancies in naturally conceived (NC) children respectively, there were 58 cases (0.53%) of atrial septal defect in ART vs. 26 cases (0.12%) in NC, 37 cases (0.34%) of changes in the interventricular septum in ART vs. 18 cases (0.09%) in NC, 20 cases (0.18%) of coarctation of the aorta vs. 13 cases (0.06%) in NC, 18 cases (0.16%) of aortic stenosis in ART vs. 11 cases (0.05%) in NC, 11 cases (0.10%) of tetralogy of Fallot in ART vs. 5 cases (0.02%) in NC, 6 cases (0.05%) of stenosis of the pulmonary trunk in ART vs. 5 cases (0.02%) in NC and 48 cases (0.44%) of other non-specified cardiac defects in ART and vs 10 cases (0.05%) in NC.…”
Section: What Is the Evidence That Arts Influence Cardiovascular Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Many are the reasons why a woman might wish to postpone pregnancy, including finding the right partner, pursuing education and career opportunities, or dealing with unexpected medical conditions. (Taitson et al ., 2014)…”
mentioning
confidence: 99%